Integration of Mahabbah Jalaluddin Rumi Values and Humanistic Education in the Formation of Student Morals at SMK Al-Munawaroh Tasikmalaya - Sumarna, Cecep; Gunawan, Heri; Hilmi, Fuad; Tehmamad, Abdulghani (IJORER : International Journal of Recent Educational Research, 2026)
Objective: The phenomenon of moral decline and increasing intolerance among students shows the existence of a spiritual crisis in modern educational practices that tend to be cognitive and instrumental. This study aims to analyze the implementation of the value of mahabbah (divine love) in education at SMK Al-Munawaroh Tasikmalaya as a strategy for the formation of social and spiritual character of students. Method: The research uses a qualitative-descriptive approach with a case study method, through in-depth interviews, participatory observations, and analysis of school policy documents. Results: The results of the study show that the value of mahabbah is implemented integratively through religious habituation, social activities, and learning based on religious moderation. This approach not only fosters empathy, tolerance, and social responsibility, but also strengthens students' spiritual awareness. These findings strengthen Carl Rogers' humanistic educational theory and extend it with Jalaluddin Rumi's sufistic dimension which places love as a force of self-and social transformation. The implementation of mahabbah has proven to be in line with national policies such as Strengthening Character Education (Perpres No. 87 Tahun 2017) and Religious Moderation (KMA No. 183 Tahun 2019). Novelty: This study concludes that mahabbah-based education can be an integrative model of humanistic Islamic education that is relevant to the context of Indonesia's pluralistic society. The implications of the study confirm the need to develop similar models in other educational units through a longitudinal approach to measure the long-term impact on the formation of students' character.